The Implementation of Bottom-Up in Reading Comprehension for Vocational School Students - Haniff, Lal Bin; Heriyawati, Dwi Fita (BRILIANT: Jurnal Riset dan Konseptual, 2024)
This research aims to investigate the improvement reading comprehension of SMK PGRI 2 Mojokerto by using Bottom-Up approach in reading comprehension of recount text. The research was conducted in two Cycles of Classroom Action Research (CAR) where each Cycle was conducted in 4 (four) phases, they were: planning, action, observation, reflection. Each Cycle was applied in (four) meetings. The subjects of the research were 35 students of tenth grade (X-C Mechatronics). In collecting data, the researcher applied three instruments: observation, questionnaire and reading test. There were 2 (two) observations in field note which conducted by the researcher: the first observation which was done before implementing Bottom-Up to find the problem during reading activity in English lesson. Meanwhile, the second observation was to find the improvement in having Bottom-Up that conducted by English teacher during the approach applied. The questionnaire was delivered to students in the fourth meeting of the second Cycle to find out the responses of the students in learning reading by using Bottom-Up. The data was analyzed through descriptive and statistical method. In this research, the researcher acted as a teacher and the English teacher as an observer. The research findings showed that the students reading comprehension improved from Cycle I to Cycle II. Furthermore, the data from the observation and questionnaire indicated that the majority of the students gave positive response toward the use of Bottom-Up approach in teaching reading. It emphasized that the approach could improve students’ ability in reading, effective, interesting, and grab the students’ enthusiasm in reading activity.